Pengaruh manajemen strategi terhadap keberlanjutan bisnis (business sustainability) pada bank umum syariah - Anita, Dinda Rosmaya (Maliki Interdisciplinary Journal, 2025)
This study aims to analyze the influence of strategic management on business sustainability in Islamic commercial banks in Indonesia. Using a conceptual-descriptive approach, it explores the relationship between corporate strategy, financial performance, and long-term sustainability. Empirical data were drawn from the 2024 report of the Financial Services Authority (OJK) and recent academic studies addressing sustainable strategy practices in Islamic banking. The findings reveal that value-based and digitally adaptive strategic management significantly contributes to improved financial performance and business resilience (Hasan & Haron, 2022; Rahman et al., 2023). Furthermore, the alignment between maqashid al-shariah principles and corporate strategies strengthens Islamic banks’ competitive positioning amidst global challenges. The study concludes that the sustainability of Islamic commercial banks depends not only on financial efficiency but also on the integration of ethical strategies, sound governance, and continuous innovation.